RANCANG BANGUN DESAIN INTERNET OF THINGS UNTUK PEMANTAUAN KUALITAS UDARA PADA STUDI KASUS POLUSI UDARA - Teguh, Rony; Oktaviyani, Enny Dwi; Mempun, Kehat Abdiel (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
Build, design and develop an Internet of Things design to monitor air quality in thewild with air pollution case studies. By utilizing the ESP-8266 type wifi modulemicrocontroller as the control center for the devices built by adding an IC4051 AnalogMultiplexer as a branching process from 1 analog channel to 7 analog channels. There are5 sensors used, namely CO (MQ-7), CO2 (Analog Infrared CO2), Dust Sensors (PM10),DHT-11 (Temperature & Humidity) and Wind speed & direction. Data recording locationand data monitoring using third party protocol, namely Ubidots.The research was conducted in 2 different locations with the time determined, namelyin the area of the UPR Informatics Engineering Department area and also in the village ofTanjung Taruna, Jabiren Raya District, Pulang Pisau Regency along with the Team of theKopernik Bali Foundation.The results of the study will be analyzed using the AQI (Air Quality Index) standardwhich is also the same as that of the BMKG as an air quality index index. By using realtimeinternet of things technology, it can make it easy to get information about the level of airquality in the wild quickly, efficiently, and the monitoring process can be done anywhereand anytime.